Scenario Planning as a Tool for Long Term Strategic Planning. The Generics Drug Industry in the European Union - Khan, Ali Zafar; Goh, Ming Tze; Kassam, Mohamed Zahir Osman (2010)
As costs associated with medical care continue to increase, and populations continue to age, member states of the EU are increasingly concerned about their long-term public spending budgets. Generic drugs have been targeted by EU policy makers as replacements to high cost pharmaceutical drugs so as to bring healthcare costs down. The EU has taken several measures in the recent past to increase competition in the generic drugs industry within the EU marketplace. As competition increases in the EU generics market over the coming years, firms within the pharmaceuticals drug industry in the region must explore new strategies so as to thrive and prosper in the long term. Decisions on making the best use of available resources must be made and strategies must be reformulated to determine actions going into the future. These long-term strategies will help companies determine their current and future positions, and ultimately, the relevant steps that they need take presently to maintain their market positions. This report seeks to analyze the current EU macro-environment and provide possible future (twenty year timeframe) scenarios to which players within the generic drugs market can prepare themselves for so as to attain a competitive position in the long-term. The scenarios that were crafted after a thorough macro environmental analysis are: the positive scenario (“Todo es Bueno!”), the negative scenario (“Nein, nicht gut!”) and the mixed scenario (“Deux Union Europeenne!”). After the scenario crafting phase, opportunities and threats were identified for the possible future scenario, and thereafter, versatile strategic recommendations were made. Based on the scenarios, the report proposes strategies and recommendations by combining the implication of the scenarios’ opportunities and threats. The report advices 7 strategies that producers can use to add value to their internal strategies and/or further examine the implication of the recommendations presented. The report argues against traditional strategic polar thinking (cost leadership or differentiation) and proposes players to use mixed strategies. It suggests producers to identify the key ingredient that differentiated themselves from competitors. It promotes investing on research to soften the blow of sudden technology changes, identify new technologies to improve business processes, and research to develop new formulation patents. It also suggests producers to invest in stakeholder management, focus on green technologies, proposes investigating the advantages of strategic manufacturing location (i.e. Turkey), and finally, suggests formulating strategic alliances to organizational learning.